Towards a new understanding of information effects on discourses and practices: The role of online newspapers in sustainable household changes. Issue 1 (1st July 2019) - Ferrucci, Martina; Petersen, Lars Kjerulf
Climate change mitigation is one of the most important societal challenges, but it is often inaccessible to direct human experience. Hence, climate change and related issues are largely constituted in the public mind from media narrations, which have the potential to push people towards new sustainable practices. This article identifies how media, in this case online newspapers, can affect pro-environmental practice changes. Firstly, we will outline a conceptual framework connecting mediatisation theories to practice theories. Secondly, we will present empirical findings for establishing connections between online news effects and sustainable practice changes and their respective recurring patterns and models.